(untitled) (American Journal of Business Management, Economics and Banking, 2024)
This article presents the findings of a student-led investigation into the correlation between music and economics. The study was conducted in a combined session involving music and economics classes. The students aimed to identify the relationship between music and economics by reviewing existing research and findings from other scientists and academics. The teachers provided relevant information and shared conclusions from empirical researches and articles. The students explored ways to implement the valuable findings in their hometowns in Uzbekistan. The article highlights the students’ efforts to bridge the gap between music and economics and their potential impact on local communities.